analytical study of the competitive excellence of the sports clubs of the Iraqi Ministry of Interior from the perspective of the employees - Al-Kaabi , Munir Abdul-Kadhim; Kadhim, Farqad Abduljabbar (Journal of Physical Education, 2026)
The study aimed to develop a measure of competitive excellence for sports clubs affiliated with the Iraqi Ministry of Interior from the perspective of employees and to identify the level of competitive excellence of these clubs from the perspective of employees. The researcher used a descriptive approach with a survey method and correlational studies. The researcher constructed a measure of competitive excellence for sports clubs from the perspective of employees, and the results were processed using SPSS statistical software. The results were presented in tables and points and discussed. The study concluded that the sports clubs of the Iraqi Ministry of Interior have a good level of competitive excellence from the perspective of employees. The researcher recommended the need to activate this administrative concept and emphasize its application in the field within sports clubs and institutions In order to lead and stay ahead of competing clubs, the administrations of sports clubs affiliated with the Iraqi Ministry of Interior should enroll their employees in advanced development and educational courses, with the aim of raising their level and job efficiency, as well as informing them of everything new in the field of distinguished sports management.